2013
DOI: 10.1007/s10897-013-9582-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct‐to‐Consumer Genetic Tests on Health Behaviour and Anxiety: A Survey of Consumers and Potential Consumers

Abstract: Direct‐to‐consumer (DTC) genetic tests can be purchased over the internet. Some companies claim to provide relative genetic risks for various diseases and thus encourage healthy behaviour. There are concerns that exposure to such information may actually discourage healthy behaviour or increase health anxiety. An online survey was conducted (n = 275). Respondents were composed of individuals who had purchased a DTC genetic test and received their results (consumers, n = 189), as well as individuals who were ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 14 publications
(39 reference statements)
2
60
1
Order By: Relevance
“…Not only have technological developments led to immense reductions in costs, they have also enabled the sequencing of the human genome in less time [5]. Accordingly, commercial companies sensed the potential and have started to offer direct-to-consumer personal genomics (DTC-PG) [8, 9]. These companies are offering personal genetic risk profiles and genomic testing outside the traditional healthcare systems and clinical settings [8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Not only have technological developments led to immense reductions in costs, they have also enabled the sequencing of the human genome in less time [5]. Accordingly, commercial companies sensed the potential and have started to offer direct-to-consumer personal genomics (DTC-PG) [8, 9]. These companies are offering personal genetic risk profiles and genomic testing outside the traditional healthcare systems and clinical settings [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, commercial companies sensed the potential and have started to offer direct-to-consumer personal genomics (DTC-PG) [8, 9]. These companies are offering personal genetic risk profiles and genomic testing outside the traditional healthcare systems and clinical settings [8, 9]. Via their websites, saliva-based tests can be purchased and based on the returned samples, selected single nucleotide polymorphisms are scanned for a variety of different complex diseases [8, 10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, there is a growing body of evidence for the effectiveness of tailored feedback in bringing about healthy behaviour change (3)(4)(5)(6) . Surveys of D-T-C services have suggested that they are effective in producing healthy behaviour change in approximately one-third of users (7)(8)(9)(10) . Awareness of D-T-C genetic tests is increasing among consumers (11) .…”
Section: What Is Personalised Nutrition?mentioning
confidence: 99%